Effect of nurse-led training on the pharmacological knowledge and management of dysmenorrhea among female undergraduates of Lagos State University ojo Lagos, Nigeria - Babarimisa, Oluwatoyin Modupeore (International Journal of Research in Medical Sciences, 2020)
Background: Dysmenorrhoea is very common among female adolescents and the associated pain could be severe and significantly impact their daily and academic lives. Dysmenorrhea can be effectively managed if properly understood and given proper management, hence, this study determined the outcome of educational intervention on pharmacological knowledge and management of dysmenorrhea among undergraduates in Lagos State University. Methods: The study utilized a one-group pre-post-test quasi experimental design. Total enumeration of 126 respondents female accounting students were selected. Two instruments of Self-Report Questionnaire (SQR) and Test Paper on Knowledge and Management of dysmenorrhea (TRKM) were used to collect data. Descriptive statistics of frequencies, percentages, mean scores and standard deviation were used to analyze the research questions. Results: Findings showed that majority of the participants 91 (72.2%) were between the ages of 20-24 years, 97 (77.0%) started menstruation between 10-15 years of age, and 76 (59.9%) only menstruated for 3 days. The pre and post intervention mean scores on knowledge of pharmacological management of dysmenorrhea were (2.981±1.176) and (8.115±0.997) with a mean gain of 6.670. Also, there is significant difference between pre and post intervention of knowledge on dysmenorrhea with knowledge gained 16.130, t=47.806 at p=0.00). Conclusions: The organized education programs on knowledge and management of dysmenorrhea benefited the participants, therefore, resulting in an increase in knowledge and management of dysmenorrhea. It was recommended that Community health practitioners, public health educators and social workers should plan appropriate technique to modify the attitude and beliefs of females on management of dysmenorrhea.